1987
DOI: 10.1111/j.1751-1097.1987.tb04793.x
|View full text |Cite
|
Sign up to set email alerts
|

SPECTROSCOPIC STUDIES OF CUTANEOUS PHOTOSENSITIZING AGENTS–XII. SPIN TRAPPING STUDY OF THE FREE RADICALS GENERATED DURING THE PHOTOLYSIS OF PHOTO ALLERGENS BITHIONOL and FENTICHLOR

Abstract: Free radicals were trapped and observed by ESR when photoallergens bithionol and fentichlor were irradiated in the presence of spin traps N‐t‐butyl‐α‐phenylnitrone (PBN) and 5,5‐dimethyl‐pyrroline‐N‐oxide (DMPO). In the absence of air, both PBN and DMPO trapped a carbon‐centered radical. The carbon‐centered radical, which was capable of abstracting a hydrogen atom from cysteine, glutathione, ethanol and formate, was identified as an aryl radical derived from the homolytic cleavage of the carbon‐chlorine bond. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
1991
1991

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Electron spin resonance spectra were acquired at room temperature with a Varian E-109 spectrometer equipped with a TM,," cavity. Irradiation was conducted in situ with a 1000 W Xe arc lamp and monochromator combination (bandpass 10 nm) as described previously (Li and Chignell, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…Electron spin resonance spectra were acquired at room temperature with a Varian E-109 spectrometer equipped with a TM,," cavity. Irradiation was conducted in situ with a 1000 W Xe arc lamp and monochromator combination (bandpass 10 nm) as described previously (Li and Chignell, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…A hand-help pump (Pipet-aid) was used as the source of air. Electron spin resonance instrumentation, optical measurements and irradiation conditions have been previously described (Li and Chignell, 1987a). The g-values were measured using a fieldlfrequency lock accessory (Varian Assoc., Palo Alto, CA) by comparison with Fremy's salt ( g = 2.0057; Wertz rl d.. 1961).…”
Section: Methodsmentioning
confidence: 99%
“…Omura and Matsuura (1971) ,have proposed that a transient intermediate, may be involved. However, our previous studies (Li and Chignell, 1987a) with the spin trap DMPO have suggested that the chlorine atoms of BT and FT are lost via a homolytic process that results in the generation of the corresponding aryl radicals (see also Grabowski, 1961). It is not possible at present to determine what role this free radical mechanism may play in the photoconversion of 4-chlorophenols to hydroquinones.…”
Section: Bi From B T and Fia And Fii From F Tmentioning
confidence: 95%
See 1 more Smart Citation